2006
DOI: 10.1017/s0022029905001561
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic study on total and partial lifetime traits for dairy ewes

Abstract: A data file on 36,396 lactations was used to determine the strength of the phenotypic relationship between productive, reproductive and lifespan traits for 7935 Spanish Churra ewes. These ewes first lambed between 1989 and 1997 and belonged to 23 flocks. The study took into account four lifespan traits (lifetime, productive life, useful life and lifetime score), three productive traits (total milk yield produced during lifetime, lambs weaned during ewe lifetime and total revenues from sold milk and weaned lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Cheese Milk ted in our study (63 to 83% in all scenarios) was similar to the range from 53 to 81% reported for dairy sheep by other investigators (Ligda et al, 2000;El-Saied et al, 2006;Tolone et al, 2011). In dairy sheep breeding flocks, the proportional contribution of milk revenue to total revenues can drop substantially on 40% due to income from sale of young breeding animals (Ligda et al, 2000) or on 38 to 50% in an open flock, while the contribution from sale of breeding animals was nearly 20% (Vlácil, 2005).…”
Section: Otherssupporting
confidence: 77%
“…Cheese Milk ted in our study (63 to 83% in all scenarios) was similar to the range from 53 to 81% reported for dairy sheep by other investigators (Ligda et al, 2000;El-Saied et al, 2006;Tolone et al, 2011). In dairy sheep breeding flocks, the proportional contribution of milk revenue to total revenues can drop substantially on 40% due to income from sale of young breeding animals (Ligda et al, 2000) or on 38 to 50% in an open flock, while the contribution from sale of breeding animals was nearly 20% (Vlácil, 2005).…”
Section: Otherssupporting
confidence: 77%
“…However, this factor is unlikely to explain the observed influence in the present study, since no lactation was allowed. Other studies have suggested that lambing month influences productive and reproductive performance of Assaf, Awassi and Churra dairy sheep, both under intensive management (Gootwine & Pollott, 2000; Pollott & Gootwine, 2004) and non-intensive management (El-Saied et al 2006). The most productive lactations started in December, March and October, which is consistent with studies suggesting that lengthening photoperiod enhances productivity and persistency (Capuco et al 2003; Pollott & Gootwine, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Ewes born in September reach puberty during the next breeding season after birth, such that their AFL falls within the ideal range of 390 to 450 d (Hernandez et al 2011). Previous studies have attributed the influence of birth month on milk productivity to the influence of photoperiod on maternal milk yield and on prepubertal growth (Gootwine & Pollott, 2000; Pollott & Gootwine, 2004; El-Saied et al 2006). However, this factor is unlikely to explain the observed influence in the present study, since no lactation was allowed.…”
Section: Discussionmentioning
confidence: 99%
“…The animals' first lambing month did not seem to influence milk production. In contrast, this factor has been found to strongly affect productive and reproductive performance of other dairy breeds (Assaf, Awassi or Churra sheep), both under intensive management (Gootwine & Pollott, 2000;Pollott & Gootwine, 2004) and non-intensive management (El-Saied et al 2006). Influence of month-ofthe-year of birth and month-of-the-year of first lambing are mostly explained by the influence of the photoperiod on maternal milk yield and hence on prepubertal growth and peripubertal breeding activity (Gootwine & Pollott, 2000;Pollott & Gootwine, 2004;El-Saied et al 2006).…”
Section: Discussionmentioning
confidence: 99%